2011
DOI: 10.1590/s1516-89132011000200024
|View full text |Cite
|
Sign up to set email alerts
|

Performance of pilot-scale vertical flow constructed wetlands with and without the emergent macrophyte Spartina alterniflora treating mariculture effluent

Abstract: Vertical flow constructed wetlands, planted with and without

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The treatment of effluent from Oncorhynchus mykiss farming by the macrophyte Phragmites australis was able to reduce the concentration of total suspended solids by 95.8 to 97.3%, total nitrogen concentration by 49 to 68.5% and total phosphorus concentration by 20.6 to 41.8% (Schulz et al, 2003). A constructed wetland colonized with the emergent macrophyte Spartina alterniflora used to treat the post-larvae effluent of the marine shrimp Litopenaeus vannamei reduced NO 2 -N (75%), NO 3 -N (35 to 55%) and P-orthophosphate concentration (59 to 64%) (Sousa et al, 2011). In addition to reducing the concentration of nutrients and suspended solids, the advantages of constructed wetlands compared to conventional systems (sedimentation ponds or lagoons or aerobic and anaerobic reactors) are lower installation costs, low energy consumption, easy maintenance and operation (Solano et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of effluent from Oncorhynchus mykiss farming by the macrophyte Phragmites australis was able to reduce the concentration of total suspended solids by 95.8 to 97.3%, total nitrogen concentration by 49 to 68.5% and total phosphorus concentration by 20.6 to 41.8% (Schulz et al, 2003). A constructed wetland colonized with the emergent macrophyte Spartina alterniflora used to treat the post-larvae effluent of the marine shrimp Litopenaeus vannamei reduced NO 2 -N (75%), NO 3 -N (35 to 55%) and P-orthophosphate concentration (59 to 64%) (Sousa et al, 2011). In addition to reducing the concentration of nutrients and suspended solids, the advantages of constructed wetlands compared to conventional systems (sedimentation ponds or lagoons or aerobic and anaerobic reactors) are lower installation costs, low energy consumption, easy maintenance and operation (Solano et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on IMTA in marine finfish aquaculture have found large reductions of nitrogen (N) and phosphorus (P) using seaweeds (Shpigel and Neori ; Chopin et al ; Schuenhoff et al ; Neori et al ; Marinho‐Soriano et al ), marine microalgae (Truesdale et al ; Allen and Watanabe ), and salt‐tolerant plants (halophytes) (e.g., Spartina spp., Aster tripolium , Suaeda esteroa , and Salicornia spp.) (Brown et al ; Brown and Glenn ; Sousa et al , ; Webb et al , ; Buhmann and Papenbrock ; Shpigel et al ; Quintã et al ).…”
mentioning
confidence: 99%